α-resolvable oriented triple systems - Tian, Zihong,; Ma, Xiuwen,; Cheng, Meihui, (Utilitas Mathematica, 2012)
An oriented triple system of order v and index λ is a-resolvable if its blocks can be partitioned into classes such that each point of the design occurs in precisely α blocks in each class. The necessary conditions for the existence of such a design are 3|αv, α|λ(v - 1). In this paper we get the spectrum of α-resolvable oriented triple systems.